Biotensegrity or Fascintegrity? - Bordoni, Bruno (Cureus, 2019)
The biotensegrity view of the living is a theoretical model and there is no mathematical study in vitro or in vivo that demonstrates its validity, taking into account the presence of liquids (blood, lymph, water), the tension produced by nerves and blood vessels, just as the displacement of the viscera and their resistances and contractions are not taken into consideration. The concept of cellular transduction is reviewed as it is the key to understanding if the passage of different mechanical information occurs only through solid structures, such as the cytoskeleton, or even liquid and viscous. The article focuses on reviewing the weaknesses of the biotensegrity model in the light of new scientific information, trying to coin another term that better reflects the dynamics of living: fascintegrity.